2017
DOI: 10.4168/aair.2017.9.4.340
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide Resistance and Its Impacts onM. PneumoniaePneumonia in Children: Comparison of Two Recent Epidemics in Korea

Abstract: PurposeThe aim of this study was to investigate the change in macrolide resistance rate in pediatric Mycoplasma pneumoniae pneumonia and to evaluate the influence of macrolide-resistant M. pneumoniae (MRMP) on the clinical course of disease, by comparing 2 recent, consecutive epidemics in Korea.MethodsA total of 250 patients with M. pneumoniae pneumonia admitted to a single tertiary hospital were enrolled in this study. Detection of MRMP was based on specific point mutations in domain V of the 23S rRNA gene. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 28 publications
3
35
0
Order By: Relevance
“…Due to the high prevalence of MRMP, there are a great deal of concerns regarding second-line treatment options for MRMP, including tetracycline or fluoroquinolones [7]. Some previous studies have reported no significant differences with respect to clinical and radiologic findings between MRMP and MSMP pneumonia in children [8,9]. When combined with the results of the present and previous studies [8,13], a considerable proportion of cases of macrolide-resistant MP pneumonia might be recategorized as clinical MSMP or MLEP pneumonia.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Due to the high prevalence of MRMP, there are a great deal of concerns regarding second-line treatment options for MRMP, including tetracycline or fluoroquinolones [7]. Some previous studies have reported no significant differences with respect to clinical and radiologic findings between MRMP and MSMP pneumonia in children [8,9]. When combined with the results of the present and previous studies [8,13], a considerable proportion of cases of macrolide-resistant MP pneumonia might be recategorized as clinical MSMP or MLEP pneumonia.…”
Section: Discussionsupporting
confidence: 45%
“…The clinical courses of MP pneumonia have shown heterogeneous features, even in patients with the same in vitro sensitivity to macrolide results [8,9,13]. Some previous studies have shown no significant differences in clinical, laboratory, and radiologic features between children with macrolide-resistant MP pneumonia and those with MSMP pneumonia [7][8][9].…”
Section: Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was not a comparative study for efficacy of corticosteroids because of no control group. We were unable to confirm MRMP strains, but other investigators in Korea have reported that the strains in the recent epidemic were MRMP strains [16,17,46]. We used corticosteroids prior to the definitive diagnosis of MP pneumonia.…”
Section: Discussionmentioning
confidence: 90%
“…The most common causes of pediatric CAP in high-income countries, which differ according to age, are Mycoplasma pneumoniae (MP) and respiratory viruses [6]. Epidemics of MP infections are repeated on a 3-7 year cycle; the last epidemic in Korea was in 2015 [7][8][9]. After 2000, macrolideresistant MP pneumonia rapidly emerged, especially in Asia [7].…”
Section: Introductionmentioning
confidence: 99%